Ethical vegetarianism : from Pythagoras to Peter Singer - Walters, Kerry S.; Portmess, Lisa, 1950- (1999)
For vegetarians seeking the historical roots of vegetarianism, for animal rights activists and the environmentally concerned, and for those questioning their consumption of meat, here's a book that provides a deep understanding of vegetarianism as more than just a dietary decision.